Study Habits of Secondary School Students in Relation to their Socio-Economic Status and Gender - Razia, B. (International Journal of Social Sciences and Management, 2015)
The study aims to explore the relationship of study habits with socio-economic status and gender. The research was carried out on a sample of 224 students studying in class IX of Aligarh district. Standardized scales were used to collect the data which in turn was analyzed by applying Mean (M), Standard Deviation (SD), Product moment correlation (r), t-test and ANOVA. Findings revealed that significant difference exists in the study habits of students in relation to gender. Significant and positive relationship exists between study habits and Socio-economic status but interaction effect of gender and SES was not found on study habits. Finally the study puts forth some suggestions to enhance the study habits of secondary school students. DOI: http://dx.doi.org/10.3126/ijssm.v2i1.11815 Int. J. Soc. Sci. Manage. Vol-2, issue-1: 68-73